Dynamic behaviour of square tubular T-joints under impact loadings. (April 2018) - Cui, Pengfei; Liu, Yanzhi; Chen, Fan; Huo, Jingsi
Abstract: This paper examines the dynamic behaviour of square tubular T-joints under impact loading by means of experimental, numerical and analytical studies. Firstly, a high-performance drop hammer setup is employed to carry out the impact tests on five hot-rolled square tubular T-joints with different chord thickness and width ratio of brace/chord under three levels of impact height. The dynamic responses of tubular T-joints including the deformation patterns and the development of impact force and displacement are described. Based on the experimental results, the impact load-deformation relationships as well as the energy dissipation are further discussed to reveal the mechanical behaviour of T-joints, with emphasis on the effect of width ratio of brace/chord and impact energy. Complementary finite element model for simulating the tubular T-joints under impact is then proposed and validated against the available test results. Finally, the test results and numerical simulations are utilized to investigate the failure mechanism of T-joints under impact load. In particular, the local and global displacements of square chord are estimated by an equivalent area method, and the impact resistance of impacted joints is examined based on the yield line theory. In general, the investigation in this paper can also offer reliable test data and design suggestions to reasonably evaluate the impact behaviour of square tubular T-joints. Highlights: Higher impact energy resulted in more evident local buckling at the chord surfaces. The width ratio of brace/chord exhibited significant effect on joint deformation modes. The proposed FE model can reasonable replicate the deformations and impact mechanisms of the square tubular T-joints. The equivalent area method provided a good evaluation of the local indentation and bending deformations. Yield line mechanism of square chord resulted in the accurate assessment of impact resistance for square tubular T-joints.